2020
DOI: 10.37213/cjal.2020.28845
|View full text |Cite
|
Sign up to set email alerts
|

Near-Native Sociolinguistic Competence in French: Evidence from Variable Future-Time Expression

Abstract: This study aims to advance the understanding of sociolinguistic competence among near-native speakers and to further knowledge about the acquisition of variable structures. We conduct a quantitative analysis of variable future-time expression in informal conversations between near-native and native speakers of French. In addition to examining linguistic constraints that have been investigated in previous research, we build on prior work by introducing a new factor that enables us to consider the role that form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Their use seems to develop with L2 proficiency, especially in an immersion context, as a result of exposure to French native input. While an exhaustive account of these studies is beyond the scope of this paper, we will detail the results of two studies that resonate with our own research questions: (Michot andPierrard 2017 andGudmestad et al 2020).…”
Section: Second Language Acquisition Of Aller + Vmentioning
confidence: 92%
“…Their use seems to develop with L2 proficiency, especially in an immersion context, as a result of exposure to French native input. While an exhaustive account of these studies is beyond the scope of this paper, we will detail the results of two studies that resonate with our own research questions: (Michot andPierrard 2017 andGudmestad et al 2020).…”
Section: Second Language Acquisition Of Aller + Vmentioning
confidence: 92%
“…Their use seems to develop with L2 proficiency, especially in an immersion context, as a result of exposure to French native input. While an exhaustive account of these studies is beyond the scope of this paper, we will detail the results of two studies that resonate with our own research questions: (Michot andPierrard 2017 andGudmestad et al 2020).…”
Section: Second Language Acquisition Of Aller + Vmentioning
confidence: 95%
“…In their 2020 study on the use of futurate forms in 10 unguided conversations between a near-native speaker and a native speaker of French, in an immersion context, and taking a variationist perspective, (Gudmestad et al 2020) found that both NS and NNSs used the periphrastic future more often than the inflectional future or the present indicative. NNSs frequently used PI in association with a temporal adverbial; and topic seriousness was identified as a variable triggering the use of inflectional future, especially among NNSs.…”
Section: Second Language Acquisition Of Aller + Vmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is now common to include task item as a random intercept in a regression to account for task-item-related variability (Winter, 2020, Section 14.4). Another change that has occurred in variationist SLA is the increased use of multinomial regression models (e.g., Gudmestad et al, 2020), which allow for the examination of three or more distinct levels of a dependent variable. The dependent variable in the current study has three levels (habitual, not-yet-occurred, both).…”
Section: Future Replication Researchmentioning
confidence: 99%